Al-alkenyl-induced formation of long-chain branched polyethylene via coordinative tandem insertion and chain-transfer polymerization using (nBuCp)2ZrCl2/MAO systems: An experimental and theoretical study. (5th July 2021) - Santoro, Orlando; Piola, Lorenzo; Mc Cabe, Karl; Lhost, Olivier; Den Dauw, Katty; Vantomme, Aurélien; Welle, Alexandre; Maron, Laurent; Carpentier, Jean-François; Kirillov, Evgueni
Graphical abstract: Highlights: The Al-alkenyl species i BuAl(oct-7-en-1-yl)2 (Al-1 ) was used as long-chain branching promoter. Ethylene polymerization with ( n BuCp)2 ZrCl2 /MAO/Al-1 was studied. Linear PE were obtained under heterogeneous conditions. Under homogeneous conditions, PE exhibited a rheological behavior indicative of LCB. The proposed LCB-formation pathway were supported by DFT calculations. Abstract: Recently, we have identified the Al-alkenyl species i BuAl(oct-7-en-1-yl)2 (Al-1 ) as a promising long-chain branching (LCB) promoter in the ethylene polymerization catalyzed by rac -EBTHIZrCl2 -based systems, proposing the incorporation of its alkenyl moiety into the growing polyethylene (PE) chain as a crucial step for LCB formation. The success of the process was attributed to the high copolymerization ability of the selected catalyst. In the present contribution, we aimed at probing the efficiency of Al-1 in combination with catalyst systems based on the unbridged metallocene ( n BuCp)2 ZrCl2 (Zr-1 ), namely homogeneous Zr-1 /MAO or heterogeneous MAO on silica-supported-Zr-1 /TIBAL (supp-Zr-1 /TIBAL); in the literature, such systems are claimed to be less efficient copolymerization catalysts compared to bridged systems (i.e. rac -EBTHIZrCl2 ). In fact, while the supported catalyst produces only purely linear PEs, branched structures were obtained in the presence of the congener homogenous system. Remarkably, the qualitative rheological data suggest that the extent of LCB formation in such samples is comparable to that of the PEs synthesized under similar reaction conditions with the EBTHI/MAO/Al-1 system. This testifies that the Al-alkenyl species is a suitable LCB promoter, even with metallocenes having quite different copolymerization ability (at least in that series). This was rationalized considering the formation of a Zr/Al heterobimetallic species facilitating the Al-1 incorporation via the coordinative tandem insertion and chain-transfer polymerization mechanism, identified in the previous study, and supported by new DFT computations.